2020
DOI: 10.1093/cz/zoaa053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of “protective” symbionts throughout the different steps of an aphid–parasitoid interaction

Abstract: Microbial associates are widespread in insects, some conferring a protection to their hosts against natural enemies like parasitoids. These protective symbionts may affect the infection success of the parasitoid by modifying behavioral defenses of their hosts, the development success of the parasitoid by conferring a resistance against it or by altering life-history traits of the emerging parasitoids. Here, we assessed the effects of different protective bacterial symbionts on the entire sequence of the host-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 50 publications
3
17
2
Order By: Relevance
“…Building upon such studies, we also show evidence of changes in host-parasite interactions due to association with a microbial mutualist. Protective symbionts are known from the plant and animal literature, and are thought to play an important role in determining host fitness (Brownlie & Johnson, 2009; May & Nelson, 2014; King et al ., 2016; Sochard et al ., 2020). Studies from agricultural plant species have shown that association with mycorrhizal fungi can reduce the negative effects of pathogens (Norman et al ., 1996; Pozo et al ., 2002; Li et al ., 2010; Song et al ., 2015; Berdeni et al ., 2018), and theoretical studies speculate as to how mycorrhizal benefits might counteract reductions in host fitness due to pathogens and affect diversity in natural communities (Bachelot et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon such studies, we also show evidence of changes in host-parasite interactions due to association with a microbial mutualist. Protective symbionts are known from the plant and animal literature, and are thought to play an important role in determining host fitness (Brownlie & Johnson, 2009; May & Nelson, 2014; King et al ., 2016; Sochard et al ., 2020). Studies from agricultural plant species have shown that association with mycorrhizal fungi can reduce the negative effects of pathogens (Norman et al ., 1996; Pozo et al ., 2002; Li et al ., 2010; Song et al ., 2015; Berdeni et al ., 2018), and theoretical studies speculate as to how mycorrhizal benefits might counteract reductions in host fitness due to pathogens and affect diversity in natural communities (Bachelot et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Protective symbionts – species that provide defensive benefits to their hosts – help determine the outcome of species interactions and, thus, shape ecological and evolutionary dynamics between hosts and parasites (Brownlie & Johnson, 2009; May & Nelson, 2014; King et al ., 2016; Sochard et al ., 2020). Despite their importance, ecological studies examining the role of protective symbionts in influencing host-parasite interactions in natural populations and communities are rare (Oliver et al ., 2014; Hafer-Hahmann & Vorburger, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A total of eight lines deriving from the three genetically distinct clones were used in this study to compare potential intra- and intergenotype differences ( Table 1 ). These lines were chosen following experiments showing evidence for differences in defensive behaviours against parasitoids between clones carrying or not carrying H. defensa [ 13 ]. Injections with H. defensa originating from different genotypes into a common aphid host genotype were done to disentangle potential host and endosymbiont effects on EBF responses.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, at least 15 different biotypes, specialised to different host plants, have been well-characterised in A. pisum , and for each biotype, different genotypes are available [ 7 , 8 , 9 ]. Thirdly, the pea aphid shows a diversity in endosymbiotic bacteria, which can be eliminated or transfected in different genetic backgrounds, and the influence of such bacteria on behavioural traits has been previously reported [ 10 , 11 , 12 , 13 , 14 ]. Finally, like other aphid species, the pea aphid reproduces parthenogenetically during most of its annual life cycle, and thus, clonal individuals can be obtained for experiments, which facilitates the dissection of genetic and environmental components of phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation